1985
DOI: 10.1073/pnas.82.8.2267
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of two cartilage-inducing factors from bovine demineralized bone.

Abstract: Two naturally occurring peptides that induce chondrogenesis in culture have been purified to apparent homogeneity. These cartilage-inducing factors (CIF-A and CIF-B) were isolated from bovine demineralized bone by dissociative extraction, gel filtration, cation-exchange chromatography, and reversed-phase HPLC. CIF-A and CIF-B at concentrations of 1-10 ng/ml each induce embryonic rat mesenchymal cells in culture to assume a cartilage morphology and synthesize cartilage-specific proteoglycan and type II collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
186
1
3

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(197 citation statements)
references
References 21 publications
7
186
1
3
Order By: Relevance
“…Mature TGF-␤ can bind to heparin (44) and our own unpublished studies indicate that LTBP1 itself binds to heparin. 3 Studies by Tiedemann et al (45) have demonstrated the importance of heparan sulfatecontaining proteoglycans in assembly of fibrillin-1 into the ECM. Thus heparan sulfate-containing proteoglycans may play a similar role in LTBP1 (and by implication TGF-␤) incorporation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature TGF-␤ can bind to heparin (44) and our own unpublished studies indicate that LTBP1 itself binds to heparin. 3 Studies by Tiedemann et al (45) have demonstrated the importance of heparan sulfatecontaining proteoglycans in assembly of fibrillin-1 into the ECM. Thus heparan sulfate-containing proteoglycans may play a similar role in LTBP1 (and by implication TGF-␤) incorporation.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (active MMP2 and MMP9) and the tissue inhibitor of the matrix metalloproteinases (TIMP1) were purchased from Oncogene Research Products (Cambridge, MA). 1,25-Dihydroxyvitamin D 3 (1,25-D 3 ) was purchased from Biomol (Plymouth Meeting, PA). Parathyroid hormone-related peptide (PTHrP) was purchased from Bachem (Torrance, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Both TGF-p1 and TGF-p2 stimulate fibroblastic, mesenchymal-like cells isolated from fetal rat muscle explants to synthesize matrix proteins characteristic of cartilage (Seyedin et al, 1985(Seyedin et al, , 1986(Seyedin et al, , 1987 and both these factors can elicit localized chondrogenesis when injected subperiosteally (Joyce et al, 1990). TGF-p1 and TGF-P2 are potent promoters of the chondrogenic differentiation of embryonic limb mesenchymal cells in vitro (Kulyk et al, 1989a;Carrington and Reddi, 1990;Schofield and Wolpert, 1990;Leonard et al, 1991) as are BMP-3 , BMP-4 (Chen et al, 1991), activin (Jiang et a]., 1993), and inhibin (Chen et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…isoform, has been purified from various natural sources including porcine platelets [3], human adenocarcinoma [4,5], human glioblastoma [6], simian epithelial kidney cells [7], bovine bone [8,9] and bovine milk [IO, has a molecular weight of approximately 25 kDa and consists of two identical polypeptide chains covalently linked by one or more disulfide bonds [4]. TGF-,82 has been shown to have important roles in mouse embryogenesis [12], wound healing (Cox, D.A.…”
Section: Esprcssio~~ Isokiicut Mtd Pur~#kurivnmentioning
confidence: 99%